MENDAMBAKAN SOSOK KEPEMIMPINAN YANG BERMENTAL DERMAWAN - Marniyati, Sabar (Universitas Surakarta, 2010)
In the face of the complex issues, including poverty problem. Indonesia needs a big and strong leader, by AB Susanto called Quantum Leadership. With the quantum-spirited leadership of a visionary leader who should be able to move and control an organization or company. In the fight against poverty in Indonesia, as now desperately needed leaders who minded philanthropist1 is a sensitive leader who has a high responsiveness in addressing social problems of society and leaders who hove high social responsibility or â!corporate social leadershipâ. A leader must be willing to either sacrifice time, energy and mind, more willing to fight for a small increase in peopleâs lives rather than personal interests.